Blastic plasmacytoid dendritic cell neoplasm: Report of two pediatric cases - Preeti Ashok Dharmani; Neha Manish Mittal; P G Subramanian; Komal Galani; Yajamanam Badrinath; Pratibha Amare; Sumeet Gujral (Wolters Kluwer Medknow Publications, 2015)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare subtype of acute leukemia that typically follows a highly aggressive clinical course in adults, whereas experience in children with this disease is very limited. We report cases of two children in whom bone marrow showed infiltration by large atypical monocytoid 'blast-like' cells which on immunophenotyping expressed CD4, CD56, HLA-DR and CD33 while were negative for CD34 other T-cell, B-cell and myeloid markers. The differential diagnoses considered were AML, T/NK-cell leukemia and acute undifferentiated leukemia. Additional markers CD303/BDCA-2 and CD123 which are recently validated plasmacytoid dendritic cell markers were done which helped us clinch the diagnosis of this rare neoplasm. An accurate diagnosis of BPDCN is essential in order to provide prompt treatment. Due to its rarity and only recent recognition as a distinct clinicopathological entity, no standardized therapeutic approach has been established for BPDCN.